Respostas de anfíbios e lagartos à degradação de matas ciliares na Amazônia Oriental - SILVA , Antonio Fernando Costa da (2016)
The innumerous current processes of habitat transformation by human actions have been recognized as the main threats to biodiversity. In this context, amphibians and reptiles have been the focus of researches, some of them observing populations decline. Our study evaluated the effects of environmental degradation in anurans and lizards in riparian forest fragments in regions with different levels of occupation in the Eastern Amazonia. Our expectation was the occurrence of changes in the structure of assemblies with the degradation. We tested the hypothesis that the richness of species more dependent on forested environments would be negatively associated to forests degradation. On the other hand, the richness of more generalists species and capable of living in the degraded forests would be positively associated with the increase in the anthropic impacts. The samplings occurred between August 2014 to September 2015 in southwest Amapa, AP (8 sample points) and north Para (4 sample points), Brazil. The sampling was by active search standardized by time. The degradation levels in the sample points were quantified using a degradation index (ID). From the 25 lizard species, 10 are heliothermics (H) and 15 no-heliothermics (nH). From the 52 amphibian species, 23 we considered from more open areas (Aa) and 29 dependent on more closed forested areas (Af). The ID varied from 0.019, in a most isolated riparian forest in Para, to 0.113 in a forest of the region closest to the urban area in Amapa. For lizards, the negative relation between nH/H and the ID was significant (F1,10 = 7.313, r² = 0.422 e p=0.022), as well as for anurans between Af/Aa and ID (F1,10 = 9.646, r² = 0.491 e p=0.011). The amphibian species dependent on forest didn’t occur in the most impacted areas. Therefore, the composition and structure of anurans and lizards assemblies in the Eastern Amazonia have been affected by degradation in the riparian forests.